Cesarean scar endometriosis: our recent experiences - Kováč, I; Novotný, M; Kováčová, K; Hribíková, Z; Belák, J (Rozhledy v chirurgii, 2021)
INTRODUCTION: Endometriosis is defined as the presence of endometrial tissue, endometrial glands or endometrial stroma outside the uterine cavity causing chronic inflammatory response. The prevalence of abdominal wall endometriosis is less than 1%. Cesarean scar endometriosis is the most common type of abdominal wall endometriosis. Chronic lower abdominal pain amplified during menstruation and palpable mass in the area of scar are the main symptoms. Generally, surgical resection with negative resection margins offers the best chance for definitive treatment of abdominal wall endometriosis. CASE REPORT: The authors present two female patients in fertile age with chronic pain in the area of Cesarean scar. The preoperatively assumed endometriosis was histologically confirmed after complete surgical excision. CONCLUSION: Abdominal wall endometriosis is rare. However, it is a possible cause of constant lower abdominal pain, impacting quality of life of the patient.
Keywords: Pregnancy; břišní stěna; těhotenství; Endometriosis; jizva; kvalita života; abdominal wall endometriosis − Pfannenstiel incision scar endometriosis − surgical resection; lidé; Female; endometrióza; ženské pohlaví; Quality of Life; císařský řez; Humans; Abdominal Wall; Cesarean Section; Cicatrix